2011
DOI: 10.1111/j.1462-2920.2011.02495.x
|View full text |Cite
|
Sign up to set email alerts
|

Key two‐component regulatory systems that control biofilm formation in Pseudomonas aeruginosa

Abstract: SummaryBiofilm formation in P. aeruginosa is a highly regulated process that proceeds through a number of distinct stages. This development is controlled by a wide range of factors, of which two-component systems (TCSs) play a key role. In this review, we focus on some of the TCSs that regulate the switch from a motile to a sessile bacterial lifestyle, either via the production of extracellular appendages or by the production of exopolysaccharides. Extracellular appendages, such as flagella, type IV pili and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
202
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(209 citation statements)
references
References 118 publications
(163 reference statements)
1
202
0
6
Order By: Relevance
“…Importantly, biofilm formation was reduced in the H. anticariensis Gac mutants compared with the wild-type, which provides evidence that these two traits are correlated in this bacterium as they are in other micro-organisms. Lately, it has been reported that in Pseudomonas aeruginosa extracellular polymeric substances play a distinct key role during biofilm formation (Yang et al, 2011) and this development is controlled by TCSs among other elements such us QS, c-di-GMP and sigma factors (Mikkelsen et al, 2011). Since biofilm formation is a complex process controlled by multiple factors, the TCS might indirectly affect it by contributing to the regulation of some key genes, all of which requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, biofilm formation was reduced in the H. anticariensis Gac mutants compared with the wild-type, which provides evidence that these two traits are correlated in this bacterium as they are in other micro-organisms. Lately, it has been reported that in Pseudomonas aeruginosa extracellular polymeric substances play a distinct key role during biofilm formation (Yang et al, 2011) and this development is controlled by TCSs among other elements such us QS, c-di-GMP and sigma factors (Mikkelsen et al, 2011). Since biofilm formation is a complex process controlled by multiple factors, the TCS might indirectly affect it by contributing to the regulation of some key genes, all of which requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the multicomponent Csr and Gac/Rsm systems inversely control attachment (and polysaccharide production and adhesiveness) and virulence, it has been suggested that they act as a genetic switch that reciprocally regulates free-swimming and surface-attached lifestyles as well as acute and chronic infections (6,107,135). Unfortunately, the signals perceived by the Gac/Rsm system or SagS are not known.…”
Section: Noncoding Rnas Mattermentioning
confidence: 99%
“…aeruginosa is an opportunistic pathogen with a broad host range and, like B. subtilis and M. xanthus, a common inhabitant of the soil (176). Biofilm formation in P. aeruginosa is typically studied in flow chambers.…”
Section: P Aeruginosa Microcolony Division Of Labormentioning
confidence: 99%
“…To understand their development, many studies have examined biofilms composed of two different strains (176,(178)(179)(180)(181)(182)(183)(184). Like in the case of M. xanthus, multiple predefined mutants were mixed to examine how these mixtures affect microcolony development.…”
Section: P Aeruginosa Microcolony Division Of Labormentioning
confidence: 99%